Alginate Content of the Seaweeds Grown in Coastal Zone of Lombok Extracted by Two Extraction Methods - Widyastuti, Sri (Jurnal Teknologi Pertanian, 2009)
Many researchers reported that seaweeds are important sources of alginate. This article reports on alginate content of seaweeds grown in coastal zone of Lombok extracted by two methods. The seaweeds were collected at several sampling points in coastal zone of Lombok, identified and analyzed their alginate content. The result shows that there were no significant different in alginate content of samples extracted using both procedures. However, only the brown species produced alginate. The alginate content more than 10% was obtained from the species of Padina sp., Dictyota sp. 1, Dictyota sp. 2, Sargassum polycistum 1, Turbinaria ornate, and Turbinaria murayana. Whereas, the alginate content less than 10% obtained from the species of Sargassum aquifolium, Sargassum sp., Turbinaria conoides, S. crassifolium, S. polycistum 2, S. Cristaefolium, and Hormophysa sp.. Therefore, it can be concluded that only the brown seaweeds had potency as alginate sources. It needed to analyze physical and chemical characteristics of this alginate related to its quality and functional application.Keywords: alginate, seaweed, extraction methods